A survey of the attitude towards research and research education among South African Ophthalmology trainees - du Toit, Linett (Division of General Surgery, 2021)
Background Completing a research dissertation or Master of Medicine (MMed) degree during ophthalmology specialist training has now become compulsory in order to qualify as an ophthalmologist in South Africa. At a national level there is currently no co-ordinated effort to standardize research training and resources for trainees. Objectives The primary objective was to determine if South African ophthalmology trainees were interested in doing research. Secondary objectives were to determine: whether they felt that their current research training was adequate; whether a national web-based research support system would be desirable; and whether such a support platform would stimulate involvement in further research once training was completed. Methods A questionnaire was designed and anonymously completed by the trainees in each training unit in South Africa. Categorical responses were summarized using crude and weighted means with 95% confidence intervals (CI). Free text responses were analyzed thematically using an inductive approach. Results Out of 81 trainees (registrars) in South Africa at the time of the survey, 64 fully completed the questionnaire - a response rate of 79%. Seventy-two percent (95% CI 57% to 87%) of the trainees reported that they were interested in doing research. Only 28% (95% CI 18% to 41%) of respondents felt that their current research training was adequate. Ninety five percent (95% CI 86% to 99%) of trainees advocate a web-based support platform would be beneficial an eighty six percent (95% CI 74% to 93%) reported such would motivate them to continue to do research once their training was complete. The themes from the qualitative data were in keeping with the quantitative results and identified variation between training institutions in terms of available research resources, supervision and allocated time to perform research. Conclusion The trainee ophthalmologists in South Africa are interested in performing research. They feel that their current research training programs are inadequate. There is a strong need for nationally standardised research guidance to eliminate the current variation between training institutions. Guidance on dedicated time allocation to complete the research component of training should be provided by regulatory bodies. A proposed web-based support system may be a good option to standardize selected available research resources and provide equal access to all trainees nationally as well as to supplement research output during and after specialist training. Further research should address the reported lack of supervision and elucidate additional barriers to performing research in South Africa.